(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Agricultural financing in West Africa remains constrained by persistent macroeconomic instability, particularly volatile consumer and producer prices that heighten credit risk and discourage lending to the agricultural sector. This study examines the asymmetric effects of price instability on agricultural financing in selected West African economies (Nigeria, Ghana, Senegal, Côte d’Ivoire, Burkina Faso, and The Gambia) over 1990–2025. Using annual panel data and the Pooled Mean Group Nonlinear Autoregressive Distributed Lag (PMG-NARDL) model, the study decomposes Consumer Price Index (CPI) and Producer Price Index (PPI) into positive and negative shocks to capture asymmetric impacts, alongside exchange rate, government expenditure, and gross capital formation. Descriptive statistics reveal substantial price volatility, while cross-sectional dependence tests confirm strong regional interdependence (p < 0.01). Unit root results indicate a mixed order of integration I(0)/I(1), justifying the econometric approach. Long-run estimates show that both CPI positive (β = −0.0487, p = 0.0017) and CPI negative (β = −0.0465, p = 0.0024) shocks significantly reduce agricultural financing, indicating that both inflationary and deflationary instability discourage credit supply. PPI positive shocks (β = 0.0103, p = 0.0198) enhance agricultural financing, while PPI negative shocks are statistically insignificant. Exchange rate depreciation reduces agricultural credit (β = −0.0521, p = 0.0003), whereas government expenditure (β = 0.0852, p < 0.01) and gross capital formation (β = 0.0247, p < 0.01) stimulate credit expansion. The error correction term (−0.3020) indicates a 30% annual speed of adjustment toward long-run equilibrium. The study concludes that macroeconomic price instability significantly constrains agricultural financing, while stable producer prices and capital formation improve credit access. Policy recommendations emphasize inflation stabilization, improved farm-gate pricing systems, efficient public expenditure, and investment led financial deepening. Limitations include reliance on aggregated macro panel data and exclusion of micro level credit behavior.